PENGARUH GREEN MARKETING MIX TERHADAP KEPUTUSAN PEMBELIAN PRODUK BEACH VOLUNTRIP DI PT. GEMILANG MEDIA WISATAMA DI YOGYAKARTA - Salsabilla, Aurora Ranting; Dewi, LGLK.; Eka Mahadewi, Ni Putu (Jurnal IPTA (Industri Perjalanan Wisata), 2023)
Green marketing mix is an important field of study for companies because it provides opportunities for competitive advantage that can influence consumer purchasing decisions. This research aims to determine the effect of green marketing mix on purchasing decisions for Beach Voluntrip product at PT. Gemilang Media Wisatama (Travelxism) partially and simultaneously. This research uses quantitative research methods and data collection techniques including observation, documentation, interviews, questionnaires, and literature study. Data analysis techniques in this research include research instrument tests, classical assumption tests, descriptive statistical analysis, multiple linear regression analysis, and hypothesis testing. The sampling technique in this research uses probability sampling technique and saturation sampling by distributing questionnaires to domestic tourists aged ? 17 years who had purchased Beach Voluntrip product at Travelxism. The results state that green marketing mix variable has a significant and positive effect on the purchasing decision variable partially and simultaneously. Based on the research results, Travelxism is advised to intensify promotions targeting tourists with an age range of 17-25 years on social media, diversify eco-friendly tourism products and provide competitive prices so they can compete with alternative tourism products and other conventional tourism products.